Trajetórias e fatores associados a qualidade de vida de mães de recém-nascidos pré-termos de muito baixo peso até três anos após o parto - Moura, Magda Regina Silva (2016)
Preterm birth is a public health problem worldwide. It holds growing global incidence rates, high mortality rates and a risk of the long-term sequelae in the newborn. It is also poses burden on the family and society. Mothers of very low birth weight (VLBW) preterm infants may develop psychological disorders, and impaired quality of life (QoL). Factors related to mothers and children in the postpartum period may be negatively associated with the QoL of these mothers. The aim of this study was to assess factors possibly associated with the QoL of mothers of VLBW preterm newborns during the first three years after birth. Mothers of VLBW preterm answered the World Health Organization Quality of Life (WHOQOL)-bref and the Beck Depression Inventory (BDI) in five time points up to 36 months postpartum, totalizing 260 observations. The WHOQOL–bref scores were compared and correlated with sociodemographic and clinical variables of mothers and children at discharge (T0) and at six (T1), twelve (T2), 24 (T3) and 36 (T4) months after the delivery. We used the Kruskal Wallis test to compared scores across different time points and correlated WHOQOL-bref scores with the sociodemographic and clinical variables of mothers and preterm infants. Multiple linear regression models were used to evaluate the contribution of these variables for the QoL of mothers. The WHOQOL–bref scores at T1 and T2 were higher when compared to scores in T0 in the physical health dimension (p = 0.013). BDI scores were also higher at T1 and T2 than those at T0 (p = 0.027). Among the maternal variables that contributed most to the QoL of mothers, there were: at T0, stable marital union (b= 13.60; p= 0.000) on the social relationships dimension, gestational age (b= 2.38; p= 0.010) in the physical health dimension; post-hemorrhagic hydrocephalus (b= -10.05; p= 0.010; b= -12.18; p= 0.013, respectively) in the psychological dimension; at T1 and T2, Bronchopulmonary dysplasia (b= -7.41; p= 0.005) and female sex (b= 8,094; p= 0.011) in the physical health dimension and environment, respectively. At T3, family income (b= -12.75’ p= 0.001) in the environment dimension, the SNAPPE neonatal severity score (b= -0.23; p= 0.027) on the social relationships dimension; at the T4, evangelical religion (b= 8.11; p= 0.019) and post-hemorrhagic hydrocephalus (b: -18.84 p: 0.001) on the social relationships dimension. The BDI scores were negatively associated with WHOQOL scores in all dimensions and at all times points: (-1.42 ≤ b ≤ -0.36; T0, T1, T2, T3 and T4). We conclude that mothers of preterm infants VLBW tend to have a transient improvement in the physical well-being during the first postpartum year. Their quality of life seems to return to levels at discharge between two and three years after delivery. The presence of maternal depressive symptoms and diagnosis of post-hemorrhagic hydrocephalus or BDP are factors negatively associated with the QoL of mothers. Social, religious and economic variables are positively associated with the QoL of mothers of VLBW preterm.